2021
DOI: 10.1128/aem.01824-21
|View full text |Cite
|
Sign up to set email alerts
|

Application of Copper Iodide Nanoparticle-Doped Film and Fabric To Inactivate SARS-CoV-2 via the Virucidal Activity of Cuprous Ions (Cu + )

Abstract: As a result of the novel coronavirus disease 2019 pandemic, strengthening control measures against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become an urgent global issue. In addition to antiviral therapy and vaccination strategies, applying available virucidal substances for SARS-CoV-2 inactivation is also a target of research to prevent the spread of infection. Here, we evaluated the SARS-CoV-2 inactivation activity of a copper iodide (CuI) nanoparticle dispersion, which provides Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…Numerous researchers have studied several materials to inactivate SARS-CoV-2 [6]. Copper iodide nanoparticles, copper-silver nanohybrids, silver nanocluster/silica com-posites, titanium dioxide, and aluminium reduce SARS-CoV-2 survival in experimental settings [4,[7][8][9]. It is not known which materials are better at decreasing SARS-CoV-2 survival in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have studied several materials to inactivate SARS-CoV-2 [6]. Copper iodide nanoparticles, copper-silver nanohybrids, silver nanocluster/silica com-posites, titanium dioxide, and aluminium reduce SARS-CoV-2 survival in experimental settings [4,[7][8][9]. It is not known which materials are better at decreasing SARS-CoV-2 survival in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Additives to plastics, metals, ceramics, and other surfaces have shown antiviral efficacy to the extent that these surfaces may have inhibitory effects after initial viral deposition. Several copper‐based products have especially attracted attention 118–131 . Some of the latter surfaces have included protective gear 121,129 .…”
Section: Coating and Impregnation Barriersmentioning
confidence: 99%
“…Several copper‐based products have especially attracted attention. 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 Some of the latter surfaces have included protective gear. 121 , 129 It is not clear how much other foreign substances may interfere with antiviral efficacy on these coated surfaces.…”
Section: Coating and Impregnation Barriersmentioning
confidence: 99%
“…Researchers theoretically demonstrated that the release of Cu (II) ions causes the destruction of viral proteins and genomes; in addition, inactivation of the virus by Cu (II) may be related to direct and indirect activity with viral surfaces via production of reactive oxygen species (ROS) [ 25 ]. Copper interferes with important virus proteins, causing their inactivation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%